1991
DOI: 10.1159/000138805
|View full text |Cite
|
Sign up to set email alerts
|

cAMP and Vascular Action of Endothelin

Abstract: Endothelin, a potent vasoconstricting peptide, induced maximal contraction of the rat tail artery within 3 min of administration. Endothelin also caused a dose-dependent decrease in tissue levels of cAMP. Concentrations of cAMP decreased about 60% 1 min after endothelin (10–8M) administration, but returned to basal levels in 5 min. By contrast, tissue levels of cGMP were not changed by endothelin. Modulation of cAMP production may provide one mechanism for the vascular action of endothelin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The local approximation condition kr ^> 1 is adopted in deriving the above equations. It is straightforward but laborious to obtain the dispersion relation from Eqs (6) ~ (11) "" + " 3 ^?r + *V +i!c|[1+r(1+n+ec2slc,: t -°^} +…”
Section: Perturbation Equations and Dispersion Relationmentioning
confidence: 99%
“…The local approximation condition kr ^> 1 is adopted in deriving the above equations. It is straightforward but laborious to obtain the dispersion relation from Eqs (6) ~ (11) "" + " 3 ^?r + *V +i!c|[1+r(1+n+ec2slc,: t -°^} +…”
Section: Perturbation Equations and Dispersion Relationmentioning
confidence: 99%
“…For example, magnetic fields have been invoked as a source of coronal heating^1 5 ' wind production^1 6 ! and high polarized radiationJ 17 ! Recently, Balbue and Hawley showed that the accretion disc with weak magnetic fields is dynamically unstable to axisymmetric disturbance.^1 8 !…”
Section: Introductionmentioning
confidence: 99%